Methylamine‐Assisted Preparation of Ruddlesden‐Popper Perovskites for Stable Detection and Imaging of X‐Rays. Issue 23 (12th September 2022) - Zhang, Min; Xin, Deyu; Dong, Siyin; Zhao, Wei; Tie, Shujie; Cai, Bing; Ma, Qingshan; Chen, Qi; Zhang, Wen‐Hua; Zheng, Xiaojia
Abstract: Sensitive and stable X‐ray detectors are essential for medical diagnostics, nondestructive industrial inspection, and security inspection. Halide perovskite X‐ray detectors are promising for direct X‐ray detection because of their high sensitivity and low limit of detection (LoD). However, their high and unstable dark current, caused by notorious ion migration in hybrid perovskites, limits their performance and long‐term operation stability. Moreover, it is still challenging to prepare high‐quality perovskite with millimeter‐thickness at a large‐scale. In this paper, solid–liquid transition of two‐dimensional (2D) Ruddlesden‐Popper (RP) perovskites enabled by methylamine gas (CH3 NH2 ) is first reported. Based on this novel approach, dense RP perovskite films with tunable ion migration and superior electronic features are produced using a lamination process. The tradeoff between stability and detection performance of perovskite X‐ray detectors is successfully solved by tuning the quantum well width of RP perovskites. X‐ray detectors with a sensitivity of 5362.3 µC Gyair −1  cm −2, LoD of 8.1 nGyair s −1 and highly working stability are achieved simultaneously. Furthermore, single gamma photon detection is realized in the RP perovskite detectors, which further confirms their capability for detecting radiation at ultralow dose rates. This study paves the way for adopting polycrystalline RP perovskites in stable X‐ray detectors. Abstract : Solid to liquid transitions of two‐dimensional Ruddlesden‐Popper halide perovskites enabled by methylamine gas treatment are reported. Structure engineering of the Ruddlesden‐Popper perovskites provides a hint for solving the tradeoff between stability and detection performance of X‐ray detectors.